WALANT as an Optimal Approach in Hand Surgery during Pandemics - Georgieva, Gordana; Srbov, Blagoja; Nikolovska, Bisera; Tusheva, Sofija; Jovanovska, Katerina; Jovanoski, Tomislav; Dzonov, Boro; Tudjarova Gjorgova, Smilja; Pejkova, Sofija (Charles University in Prague, Karolinum Press, 2022)
The emergence of the COVID-19 pandemic imposed fundamental changes in the field of surgery. Reorganization was made in order to adequately treat the patients during the pandemic. WALANT (Wide Awake Local Anesthesia No Tourniquet) approach was found to be a very convenient method in facilitating continuity in hand surgery with limited staff. A retrospective comparative study was performed between period of April 2020 till September 2021 at our clinic to evaluate advantages of WALANT approach. This study included 136 patients, from which 72 (53%) were operated with WALANT, compared to the control group of 64 (47%) patients without WALANT. Average hospital stay for the WALANT group was 2.2 days vs. 4.7 days for the control group. Average operating room personnel were 3.8 for WALANT and 6.2 for the control non-WALANT group. Intraoperative and postoperative VAS (visual analogue scale) score was evaluated. Due to its diversity, low cost and low complication rate, we recommend WALANT approach in acute and elective hand surgery.
Keywords: COVID-19; Hand surgery; Hand trauma; WALANT